Proposition of a theoretical model for leisure practices based on constraints and attitudes - Andrade R.D. (2024)
© 2023 World Leisure Organization.This study proposes a theoretical model for leisure practices based on constraints and attitudes towards leisure. The instruments applied were the Leisure Practices Scale, Leisure Attitude Scale, and Leisure Constraint Scale. The sample comprised 992 industrial workers in the Greater Florianopolis, Brazil. The proposed model consists of a quadrant based on a combination of constraint variables (low to high levels) and attitude variables (positive to negative). The best conditions for engaging in leisure practices were a combination of low constraints and positive attitudes (Q4). A second group, characterized by high constraints and positive attitudes (Q2), was considered to have favoruable conditions for participation in leisure activities. Subjects with low constraints and negative attitudes (Q3) were considered to be in a slightly unfavourable condition, whereas groups at risk of low involvement in leisure practices had high constraints and negative attitudes (Q1). The proposed model explained the greater or lesser involvement of individuals in leisure practices based on constraint and attitude variables. Repercussions of the relation between constraint and attitude variables on leisure participation are discussed herein.